2015
DOI: 10.3354/meps11114
|View full text |Cite
|
Sign up to set email alerts
|

Stock structure of Atlantic herring Clupea harengus in the Norwegian Sea and adjacent waters

Abstract: The genetic structure of Atlantic herring Clupea harengus was investigated in its north-easterly distribution at the Norwegian Sea and adjacent waters, using 23 neutral and one non-neutral (Cpa111) microsatellite loci. Fish from the two main suspected populations, the Norwegian spring-spawning herring (NSSH) and the Icelandic summer-spawning herring (ISSH), were collected at spawning locations/seasons from 2009 to 2012. Samples were also collected from Norwegian autumn spawning locations and from different loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 73 publications
1
25
0
Order By: Relevance
“…The nuclear‐coding rhodopsin gene is a powerful tool in the identification of closely related fish species (Rehbein ; Pampoulie et al . ), and here, we found that only seven of 160 specimens (4%) analysed at both mtDNA and rhodopsin yielded ambiguous assignment to their lineage of origin (Table S2, Supporting information). Interestingly, two of these individuals possessed double peaks, or heterozygous indels, in the rhodopsin chromatograms (Fig.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The nuclear‐coding rhodopsin gene is a powerful tool in the identification of closely related fish species (Rehbein ; Pampoulie et al . ), and here, we found that only seven of 160 specimens (4%) analysed at both mtDNA and rhodopsin yielded ambiguous assignment to their lineage of origin (Table S2, Supporting information). Interestingly, two of these individuals possessed double peaks, or heterozygous indels, in the rhodopsin chromatograms (Fig.…”
Section: Discussionmentioning
confidence: 67%
“…Similarly, five samples caught in deep waters (FW1dp07_7.6,FW1dp07_7.8,FW2dp07_ 7.15,FW2dp07_7.21 & IrNEdp06_29) exhibited clade A haplotypes but possess multilocus microsatellite genotypes falling within the 'deep' group. The nuclear-coding rhodopsin gene is a powerful tool in the identification of closely related fish species (Rehbein 2013;Pampoulie et al 2015), and here, we found that only seven of 160 specimens (4%) analysed at both mtDNA and rhodopsin yielded ambiguous assignment to their lineage of origin (Table S2, Supporting information). Interestingly, two of these individuals possessed double peaks, or heterozygous indels, in the rhodopsin chromatograms ( Fig.…”
Section: Population Structure and Connectivitymentioning
confidence: 73%
“…() observed differences between the Icelandic summer spawners and populations from Scotland and Canada. No genetic differentiation was found among the spawning populations (I, F, M, L and S) assessed in this study in an analysis of 24 microsatellite markers (Pampoulie et al ., ), which suggests that the differentiation among the populations may be recent or environmentally determined. Studies on North Sea and Baltic Sea C. harengus populations have been found to be weakly genetically structured (Bekkevold et al ., ; Gaggiotti et al ., ; Teacher et al ., ), but most of the observed patterns were explained by microsatellite loci that were possibly under selection, linked to salinity differences (Gaggiotti et al ., ; Teacher et al ., ), or to temperature and oceanographic connectivity (Teacher et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the population structure of Atlantic herring can be complex (Iles & Sinclair 1982) ranging from migratory oceanic populations to stationary local populations. Some of these populations can be genetically distinguished (Bekkevold et al 2007, Pampoulie et al 2015. Further, populations within the Baltic Sea are structured according to the salinity gradient (Bekkevold et al 2005, Jørgensen et al 2005.…”
Section: Introductionmentioning
confidence: 99%